Delivery outcome after trial of labor in nulliparous women 40 years or older—A nationwide population‐based study. (19th April 2019) - Ankarcrona, Victoria; Altman, Daniel; Wikström, Anna‐Karin; Jacobsson, Bo; Brismar Wendel, Sophia
Abstract: Introduction: The number of women postponing childbirth until an advanced age is increasing. Our aim was to study the outcome of labor in nulliparous women ≥40 years, compared with women 25‐29 years, after both spontaneous onset and induction of labor. Material and methods: The nationwide population‐based Swedish Medical Birth Register was used to study the perinatal outcome in nulliparous women with a singleton, term (gestational weeks 37‐44), live fetus in cephalic presentation and a planned vaginal delivery from 1992 to 2011. We included 7796 nulliparous women ≥40 years and 264 262 nulliparous women 25‐29 years. Prevalence and risk of intrapartum cesarean section, operative vaginal delivery, obstetric anal sphincter injury and a 5‐minute Apgar score <7 were calculated for women ≥40 years stratified for spontaneous onset and induction of labor, using women 25‐29 years as the reference in both strata. Crude and adjusted odds ratios (aOR) were calculated by unconditional logistic regression and presented with 95% confidence intervals (CI). Results: Overall, 79% of women ≥40 years with a trial of labor reached a vaginal delivery. After spontaneous onset, intrapartum cesarean section was performed in 15.4% of women ≥40 years compared with 5.4% of women 25‐29 years (aOR 3.07, 95% CI 2.81‐3.35). Operative vaginal delivery was performed in 22.3% of women ≥40 years compared with 14.2% of women 25‐29 years (aOR 1.71, 95% CI 1.59‐1.85). After induction of labor, an intrapartum cesarean section was performed in 37.2% women ≥40 years compared with 20.2% women 25‐29 years (aOR 2.51, 95% CI 2.24‐2.81). Operative vaginal delivery was performed in 22.6% of women ≥40 years compared with 18.4% women 25‐29 years (aOR 1.45, 95% CI 1.28‐1.65). The risk of obstetric anal sphincter injury or a 5‐minute Apgar score <7 was not increased in women ≥40 years, regardless of onset of labor. Conclusions: Trial of labor ended in vaginal delivery in 79% of nulliparous women ≥40 years. The risks of intrapartum cesarean section and operative vaginal delivery were higher in women ≥40 years compared with women 25‐29 years, after both spontaneous onset and induction of labor. The risk of obstetric anal sphincter injury or a 5‐minute Apgar score <7 was not increased.